Influence of Pressure on Water Permeability and Characteristic Opening Size of Nonwoven Geotextiles (Journal of Fiber Bioengineering and Informatics, 2013)
Nonwoven geotextiles manufactured by mechanical carding process and bonding by needling processare investigated in this paper. Part of the samples was additionally bonded by thermal calendaringprocess. Sampling was conducted according to the standard for geotextile with certain modifications.The samples were tested for water permeability perpendicular to the plane of samples using loads of 2,20 and 200 kPa. Characteristic opening size of geotextiles was tested using sieving method. Researchshows that different applied pressures significantly change structure and properties i.e. thickness andwater permeability normal to the plain under load of geotextile.